Wettersatellitenbild und klimaökologische Zonierung.: Ein kritischer Beitrag zur Bedeutung des Satellitenbildes für geographische Fragestellungen am Beispiel Tropisch-Westafrikas - Lauer, Wilhelm; Breuer, Toni (ERDKUNDE, 1972)
This work examines the extent to which the daily radio photos from weather satellites can be used by geographers for non-meteorological purposes. An interpretation of satellite pictures oriented to terrestrial structures can hardly be based on conventional methods, unlike the conventional air photograph which has long been indispensable as a tool of geographical research. The enormous height at which satellites fly and the consequently limited amount of disaggregation possible with weather satellite pictures permit only investigations which differentiate shading. Thus contrast is the most important criterion for the interpretation of satellite pictures. All shadings are only a relative expression of differences. In order to arrange the tonal differences on an air photo clearly into specific ranges of a density scale, a socalled equidensity film was used. This enables a photograph to be split up into areas of equal density. Using this method it was possible to identify, on satellite photographs of West Africa, the stepwise sequence of various shading belts between the Sahara and the rain forests near the Equator, almost corresponding to lines of latitude. There is here an obvious parallel to the relevant climatic zones. Further work was carried out on selected individual structures shown on the satellite pictures of the area studied. The last step was to test the extent to which the pictures could show seasonal changes in this area. Photo extracts of the Sahel Zone are presented to show changing seasonal rhythm.